The Neenan Company: rebuilding from a crisis. Issue 2 (5th May 2016) - Albert, Lumina S.; Wright, Grace Hanley; Dean, Thomas J.
Abstract : Synopsis: The Neenan Company is a construction firm based in Fort Collins, Colorado, known for their efforts in pioneering the advancement of the design/build approach to construction. With a history of industry leadership, innovative contracting methods, and ethical business practices, the company now faces management, customer relations, and financial challenges. Serious structural problems were discovered in a number of public schools and other buildings built by the company. Thrown into a whirlwind of shock, Randy Myers, President of the company, must consider how to respond to the crisis, and how to prevent these issues in the future. Written from his perspective, this case provides a platform for considering the challenges that can result from industry innovation, ethical decision-making, and crisis management. Research methodology: For the development of this case, the authors interviewed the top management at the Neenan Company: Founder David Neenan, President Randy Myers, and Donna Smith, Vice President of Business Development. The authors also interviewed current employees, previous employees of Neenan, representatives of school buildings built by Neenan, stakeholders, other experts in the construction field and existing customers of the company. The company made internal documents available to the authors, including financial statements and quality control and assessment tools, which were provided by Ryan Dellos, Chief Financial Officer. The authors surveyed financial documents and business documents to analyze pertinent information and data relevant to the case. All the interviews were recorded, coded, and analyzed to include multiple perspectives. Extensive online research was conducted on the construction industry and The Neenan Company which included several news articles and interviews on David and Randy. Additionally, the authors carefully studied the news reports by The Denver Post and other related press materials. Experts from the construction field and financial field provided assistance with data analysis and interpretation. The authors used a variety of academic resources to draw connections between the issues faced by Neenan and concepts discussed in business courses. Relevant courses and levels: This case has applications in entrepreneurship, small business management, business ethics, leadership, organizational structure/design, and new venture management courses at both undergraduate and graduate levels. It also contains critical areas of decision-making relevant to an advanced strategic management course. The case can be introduced at any stage of the term, and is specifically relevant to discussions focussing on innovation and growth, corporate social responsibility, ethical decision-making, stakeholder theory, entrepreneurial crisis management, and long-term venture success.